Scaling up Sustainable Agriculture and Food Security With Nanoscience and Technology - Goshen David Miteu; Olayemi Ojeokun; Irenosen Addeh; Afolabi Ayomide; Temidayo Olayinka; Sunday Godwin James; Oluwatobi Adeyemo; Elohozino Oghale Benneth (Modern Agriculture)
ABSTRACT Agriculture has been the primary source of food for humanity since time immemorial. With the ever‐growing global population and the rising demand for food supplies, there has been a transition from traditional agricultural practices to more advanced methods. Nanoscience and technology represent a cutting‐edge approach that offers numerous benefits. This review narrates the importance of incorporating nanoscience and technology into agriculture to manipulate matters for sustainable agriculture and food security. This study will also serve as a valuable resource for agriculturalists in developing countries, providing them with a better understanding of the potential of nanoscience and technology in agriculture, ultimately contributing to improved food production and global food security.